1998
DOI: 10.1007/s002620050486
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer cell vaccine prepared with replication-deficient vaccinia viruses encoding B7.1 and interleukin-2 induce antitumor response in syngeneic mice

Abstract: A replication-deficient recombinant vaccinia virus, NYVAC, was developed by deleting 18 open reading frames in the vaccinia virus genome. Recombinant NYVAC, encoding the murine T cell co-stimulatory gene B7.1 (CD 80) (NYVAC-B7.1) and the murine interleukin-2 gene (NYVAC-IL-2), were prepared and the expression of B7.1 and the secretion of IL-2 were respectively confirmed in vitro. The use of these viruses to prepare a potent tumor cell vaccine was studied in a syngeneic murine CC-36 colon adenocarcinoma model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…NYVAC is an attenuated derivative of the VACV Copenhagen strain (CopV), from which 18 open reading frames (ORFs) were specifically deleted from the parental viral genome, including those involved in host range, virulence, and pathogen-esis (13). NYVAC-derived vectors are able to express antigens from a broad range of species (13) and have been used as recombinant vaccines against numerous pathogens and tumors (1,(14)(15)(16), and phase I/II clinical trials using NYVAC against HIV-1 have shown strong and specific immunogenicity and a good safety profile (17). The most frequently studied nonattenuated VACV strain is Western Reserve (WR), a mouse brain-passaged derivative of the New York Board of Health (NYBH) vaccinia virus (18), one of the most widely used vaccinia viruses in the smallpox eradication program and the basis of the only commercially approved smallpox vaccine (Dryvax) available for limited use in the United States (19).…”
Section: Importancementioning
confidence: 99%
“…NYVAC is an attenuated derivative of the VACV Copenhagen strain (CopV), from which 18 open reading frames (ORFs) were specifically deleted from the parental viral genome, including those involved in host range, virulence, and pathogen-esis (13). NYVAC-derived vectors are able to express antigens from a broad range of species (13) and have been used as recombinant vaccines against numerous pathogens and tumors (1,(14)(15)(16), and phase I/II clinical trials using NYVAC against HIV-1 have shown strong and specific immunogenicity and a good safety profile (17). The most frequently studied nonattenuated VACV strain is Western Reserve (WR), a mouse brain-passaged derivative of the New York Board of Health (NYBH) vaccinia virus (18), one of the most widely used vaccinia viruses in the smallpox eradication program and the basis of the only commercially approved smallpox vaccine (Dryvax) available for limited use in the United States (19).…”
Section: Importancementioning
confidence: 99%
“…This vector has been applied as a recombinant vaccine delivery system in animal models and target species, including humans (34,37). NYVAC-based vectors have been analyzed as vaccines for several tumors (23,46) and are protective against pathogens such as retroviruses (5, 10, 31), Japanese encephalitis virus (24), and Plasmodium falciparum (34). The potential use of variola virus as a biological weapon requires the development of safer smallpox vaccines, using attenuated VV strains such as MVA and NYVAC (4, 9).…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins (100 g) were separated by SDS-PAGE, transferred to nitrocellulose, and immunoblotted at various times (6 and 16 hpi) with an anti-caspase-9 antibody (Oncogene) that recognizes the procaspase and the cleaved active form of caspase-9. Caspase-9 presented a proform (46 (Fig. 5A, lower panels).…”
Section: Fig 2 Nyvac-induced Apoptosis In Hela Cells (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell surface co-stimulatory molecules such as B-7 have been introduced into tumour cells to enhance their co-stimulatory capacity (Chen et al, 1992;Raes et al, 1998) but were found to be of similarly restricted effectiveness. In consequence, combinations of cytokines and cell surface co-stimulatory molecules are now being evaluated in pre-clinical and clinical studies (Sivanandham et al, 1998).…”
mentioning
confidence: 99%